Association of Diet Quality Measured by Three A Priori-Defined Dietary Patterns With Gut Microbiota and Intestinal Permeability Among Obese Individuals. (14th June 2022) - Eaton, Sarah; Rasmussen, Heather; Chai, Weiwen
Abstract: Objectives: The human gastrointestinal tract (GI) may play a critical role in the prevention of obesity and metabolic diseases. Considering the importance of a healthy diet for optimal health, this study examined associations of diet quality assessed by three a priori-defined dietary patterns (Healthy Eating Index 2010 [HEI-2010], Mediterranean Eating Pattern for Americans [MEPA], and Dietary Approaches to Stop Hypertension [DASH] with gut microbiota, short-chain fatty acids (SCFA) and intestinal permeability markers in adult obese participants. Methods: Analyses utilized baseline data from 103 obese subjects (43.8 ± 11.3 years, body mass index ≥30 kg/m 2, 72.8% females, 64.1% blacks) who participated in a probiotic/prebiotic supplement trial. Diet was assessed using a validated food frequency questionnaire. Associations of diet quality with outcome measures were assessed using partial correlation coefficient adjusting for relevant covariates. General linear models (GLM) were applied to compare covariate-adjusted means of outcomes for tertiles of respective dietary patterns scores. Results: Scores of HEI-2010 (r = 0.25, P = 0.02), MEPA (r = 0.24, P = 0.03) and DASH (r = 0.28, P P = 0.008) were positively associated with Blautia abundance. HEI-2010 score was positively associated butyrate and propionate to total SCFA ratio (r = 0.24, P = 0.048). Intestinal permeability marker, urinary 24-hr sucralose levels were inversely associated with HEI-2010 (r= −0.30, P = 0.009) and MEPA (r= −0.26, P = 0.02) score. The results were similar when GLM models were performed. No significant associations were observed between scores of dietary patterns and measures of microbial diversity. Conclusions: Blautia abundance and inversely associated with intestinal permeability markers such as urinary 24-h sucralose levels suggesting diet quality may have positive impact on the human GI community. Funding Sources: No funding support.